The Dirt: Industrial Disease and Conflict at St. Lawrence, Newfoundland - Lewchuk, Wayne (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2011)
The article reviews the book, "The Dirt: Industrial Disease and Conflict at St. Lawrence, Newfoundland," by Rick Rennie.